2016
DOI: 10.1080/15309576.2015.1137771
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Performance Feedback and Job Autonomy in Mitigating the Negative Effect of Role Ambiguity on Employee Satisfaction

Abstract: The job demands-control (JDC) model suggests that job demands and job control (job autonomy) combine interactively in predicting job-related outcomes. While the model has been widely tested, studies using it have often failed to demonstrate the predicted interaction effects of job demands and job control on measures of a wide range of outcomes. The current study proposes performance feedback as a different situational variable that could relate to job demands and job control, and examines the three-way interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 64 publications
0
25
0
3
Order By: Relevance
“…Some use a single-item, “Considering everything, how satisfied are you with your job?” to measure job satisfaction (Bae & Kim, 2016; Fernandez & Moldogaziev, 2015). Others add an additional item: “Considering everything, how satisfied are you with your organization?” to construct a two-item composite measure (Jong, 2016; Pitts, 2009). In the sample of their meta-analysis on job satisfaction, Cantarelli et al (2016) find that about one fourth of the studies uses a single-item and the rest use multiple-item measures, and some work suggests that multi-item measurements tend to produce a more conservative and accurate estimate of overall job satisfaction (Oshagbemi, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Some use a single-item, “Considering everything, how satisfied are you with your job?” to measure job satisfaction (Bae & Kim, 2016; Fernandez & Moldogaziev, 2015). Others add an additional item: “Considering everything, how satisfied are you with your organization?” to construct a two-item composite measure (Jong, 2016; Pitts, 2009). In the sample of their meta-analysis on job satisfaction, Cantarelli et al (2016) find that about one fourth of the studies uses a single-item and the rest use multiple-item measures, and some work suggests that multi-item measurements tend to produce a more conservative and accurate estimate of overall job satisfaction (Oshagbemi, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…This is beneficial for practitioners and researchers to maintain a sustainable management environment. For example, both autonomy and feedback can be studied simultaneously with the job characteristics model [88,89] and the inconsistencies between individual performance and team performance [90].…”
Section: Limitations and Further Studymentioning
confidence: 99%
“…It has been known that supervisor feedback plays a role in changing their subordinates’ attitudes and behaviors. Previous studies have indicated that employees who receive performance or developmental feedback from their supervisors are likely to display positive behavioral and attitudinal outcomes, such as organizational citizenship behavior (OCB; Peng and Chiu, 2010 ), organizational commitment (OC; Eisenberger and Stinglhamber, 2011 ), trust ( Nyhan, 2000 ), job satisfaction ( Jong, 2016 ), and performance improvement ( Favero et al, 2014 ). However, relatively little empirical research has examined the role of supervisor feedback on IWB, and its effects on IWB is veiled.…”
Section: Introductionmentioning
confidence: 99%